HUBUNGAN TINGKAT PENGETAHUAN LANSIA TENTANG RISIKO TERJADINYA OSTEOPOROSIS DENGAN UPAYA PENCEGAHAN DI UPT PUSKEMAS DELITUA KABUPATEN DELI SERDANG - Tinah Tinah; Fauzi Romeli; Emi Inayah Sari Siregar (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2026)
Background: Osteoporosis is a disease characterized by low bone mass, accompanied by changes in bone microaxecture and a decrease in the quality of bone tissue, which ultimately causes bone fragility and risk of fracture. Objective: To determine the level of knowledge of elderly people about the risk of osteoporosis at the Delitua Community Health Center . Method: This type of research is quantitative analytical with a cross sectional research design. The population in this study were 50 elderly people at the UPT Delitua Community Health Center, Deli Serdang Regency, who suffered from osteoporosis. The sampling technique in this research is Total Sampling. Data collection was carried out using a questionnaire. Results: The results of the study showed that of the 50 respondents, the majority of elderly people had sufficient knowledge (54%), and prevention efforts were in the good category (70%). Conclusion: There is a relationship between the level of knowledge of elderly people about the risk of osteoporosis and prevention efforts at the UPT Delitua Health Center, Deliserdang Regency in 2024. Using the chi-square test, the p value was 0.000. Suggestion: It is hoped that the elderly will care more about their health and that the elderly should always maintain a healthy diet, such as consuming foods that contain calcium, not consuming alcohol, exercising diligently and controlling their health on time.